The role of green finance and governance effectiveness in the impact of renewable energy investment on CO₂ emissions in BRICS economies - Ashutosh Yadav; Bright Akwasi Gyamfi; Simplice Asongu; Deepak Kumar Behera (African Governance and Development Institute (AGDI), 2024)
In the context of sustainable development, this study investigates the intricate dynamics among good governance, renewable energy investment, and green finance in BRICS nations. The aim of the study is to assess how green finance and governance effectiveness moderate the impact of renewable energy investment on CO2 emissions. Utilizing the Cross-Sectional Autoregressive Distributed Lag (CS-ARDL) model, a meticulous analysis spanning two decades was conducted to unravel the relationships among key variables and CO2 emissions. The findings underscore a nuanced interplay where renewable energy investments, synergized with robust governance and strategic green finance, significantly mitigate CO2 emissions, contributing to sustainable economic development. However, the study reveals non-linear relationships, highlighting the necessity for optimal allocation and strategic planning to maximize environmental benefits. In the short-run, a government effectiveness policy threshold that should be attained in order for renewable energy investment to reduce CO2 emissions is provided. In the long-run, the negative responsiveness of CO2 emissions to renewable energy investment is further consolidated by green finance. Moreover, enhancing renewable energy investment in the long run is positive for environmental sustainability. It follows that policy makers should tailor policies aimed at enhancing renewable energy investment in the long-run as well as complementing renewable energy investment with green finance in the long-run in order to ensure environmental sustainability by means of reducing CO2 emissions. Policymakers in BRICS nations are urged to strengthen governance structures, promote renewable energy investments, leverage green finance, foster public-private partnerships, adopt a holistic approach, and address non-linear effects to accelerate the transition to a low-carbon economy.
Keywords: 330; Sustainable Development; Governance; Renewable Energy Investment; BRICS and CS-ARDL